2003
DOI: 10.1002/j.1556-6978.2003.tb01812.x
|View full text |Cite
|
Sign up to set email alerts
|

Supervisor and Supervisee Attachments and Social Provisions Related to the Supervisory Working Alliance

Abstract: The purpose of this study was to examine the relationship between supervisors' and supervisees' self‐reported ability to make healthy adult attachments in relationships, social provisions, and the perceptions of the supervisory working alliance. Data from 67 supervisee‐supervisor dyads indicated that supervisees' social provisions and ability to make healthy adult attachments did not predict supervisees' or supervisors' perceptions of the working alliance at a statistically significant level, but the superviso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
72
0
4

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(81 citation statements)
references
References 30 publications
5
72
0
4
Order By: Relevance
“…Overall, the results of the analysis regarding the ideal mentor revealed that when given the opportunity to express their perceptions openly and at length, mentors and interns alike refer first and foremost to professional and personal traits, to the mentoring relationship, and to the mentor's attitudes toward the role. These seem to be essential preconditions and dispositions perceived as necessary to the role and are also mentioned in the professional literature (e.g., CACREP, 2001; Israeli Ministry of Education, Division of Psychological and Counseling Services, 2000; Nelson & Johnson, 1999;SINACES, 1993;Studer, 2005;Tentoni, 1995;White & Queener, 2003). The priority attributed to professional traits by both groups indicates that the respondents consider that the profession of counseling should be learned from highly effective, experienced, and well-established professional counselors.…”
Section: Discussionmentioning
confidence: 95%
“…Overall, the results of the analysis regarding the ideal mentor revealed that when given the opportunity to express their perceptions openly and at length, mentors and interns alike refer first and foremost to professional and personal traits, to the mentoring relationship, and to the mentor's attitudes toward the role. These seem to be essential preconditions and dispositions perceived as necessary to the role and are also mentioned in the professional literature (e.g., CACREP, 2001; Israeli Ministry of Education, Division of Psychological and Counseling Services, 2000; Nelson & Johnson, 1999;SINACES, 1993;Studer, 2005;Tentoni, 1995;White & Queener, 2003). The priority attributed to professional traits by both groups indicates that the respondents consider that the profession of counseling should be learned from highly effective, experienced, and well-established professional counselors.…”
Section: Discussionmentioning
confidence: 95%
“…The nature of this relationship can serve as an important model and set standards for the way interns will create rapport and working alliances with their own clients. Moreover, the development of confidence in the therapeutic role is considered to be a direct result of the quality of the mentoring relationship (cf., White & Queener, 2003). Hence, the need for both parties to invest in creating a successful mentoring relationship and to foster its development into a fruitful working alliance is vital.…”
Section: Discussionmentioning
confidence: 98%
“…While there is quite an extensive literature dealing with supervision of counselors, most of it focuses on supervision provided by faculty members within academic institutions (cf., Freeman & McHenry, 1996;Prieto, 1998), or on post-degree supervision of school counseling practitioners (cf., Sutton & Page, 1994;White & Queener, 2003). Relatively few research studies focus specifically on the role and standards of behavior in regard to on-site school-based mentoring.…”
Section: Introductionmentioning
confidence: 97%
“…The study by Wester et al (2004) on male supervisees' restricted emotionality found that within the context of the supervisory relationship, male supervisees with higher levels of restricted emotionality were more likely to deal with psychological distress by becoming depressed or developing low self-esteem; however, they did not specifically examine the association between restricted emotionality and the SWA. In their study on attachment style and SWA among supervisory dyads, White and Queener (2003) found that only the supervisor's attachment style positively predicted both supervisor and supervisee perceptions of the working alliance. Similarly, Riggs and Bretz (2006) found that regardless of the supervisee's attachment style, the supervisor's attachment style was significantly associated with the tasks and bond of the working alliance.…”
Section: Determinants Of the Supervisory Relationshipmentioning
confidence: 96%
“…Yet, with the exception of male restricted emotionality (Wester et al 2004), adult attachment (Kim and Birk 1998;Riggs and Bretz 2006), and trainee and supervisor emotional well-being (White and Queener 2003), limited studies have examined the impact of supervisor or trainee personality traits (i.e., personality patterns, emotional well-being, and attitudes and values) on the supervisory relationship itself. The study by Wester et al (2004) on male supervisees' restricted emotionality found that within the context of the supervisory relationship, male supervisees with higher levels of restricted emotionality were more likely to deal with psychological distress by becoming depressed or developing low self-esteem; however, they did not specifically examine the association between restricted emotionality and the SWA.…”
Section: Determinants Of the Supervisory Relationshipmentioning
confidence: 99%